Hemolytic Membrane Vesicles of Group B Streptococcus Promote Infection - Armistead, Blair (J Infect Dis, 2020)
BACKGROUND: Group B streptococci (GBS) are β-hemolytic, Gram-positive bacteria associated with fetal injury, preterm birth, spontaneous abortion, and neonatal infections. A key factor promoting GBS virulence is the β-hemolysin/cytolysin, a pigmented ornithine rhamnolipid (also known as granadaene) associated with the bacterial surface. METHODS: A previous study indicated that GBS produce small structures known as membrane vesicles (MVs), which contain virulence-associated proteins. In this study, we show that GBS MVs are pigmented and hemolytic, indicating that granadaene is functionally active in MVs. RESULTS: In addition, MVs from hyperhemolytic GBS induced greater cell death of neutrophils, T cells, and B cells compared with MVs from isogenic nonhemolytic GBS, implicating MVs as a potential mechanism for granadaene-mediated virulence. Finally, hemolytic MVs reduced oxidative killing of GBS and aggravated morbidity and mortality of neonatal mice infected with GBS. CONCLUSIONS: These studies, taken together, reveal a novel mechanism by which GBS deploy a crucial virulence factor to promote bacterial dissemination and pathogenesis.